2009
DOI: 10.1177/1756287209350383
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder in males

Abstract: The prevalence of overactive bladder (OAB) symptoms is considerable in both men and women and the impact on quality of life (QOL) is equally substantial. Ironically, despite nearly equal prevalence, OAB symptoms in men are infrequently treated, and often with medical therapies aimed at bladder outlet obstruction (BOO). In this review, we examine the pathophysiology of OAB and its evaluation in the context of benign prostatic hypertrophy and concomitant BOO. We then consider the efficacy and safety of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…12 At the molecular physiological level bladder wall thickening can be due to excessive extracellular matrix production and deposition, detrusor cellular growth, hyperplasia and hypertrophy, as well as increased inflammatory responses. 13,25,26 Type I collagen, one of the main constitutive proteins contributing to bladder hypertrophy, is regulated at least in part by increased endogenous NGF in the bladder during cystitis. 13 This study shows that NMDAR activation also contributes to type I collagen up-regulation in the bladder during cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…12 At the molecular physiological level bladder wall thickening can be due to excessive extracellular matrix production and deposition, detrusor cellular growth, hyperplasia and hypertrophy, as well as increased inflammatory responses. 13,25,26 Type I collagen, one of the main constitutive proteins contributing to bladder hypertrophy, is regulated at least in part by increased endogenous NGF in the bladder during cystitis. 13 This study shows that NMDAR activation also contributes to type I collagen up-regulation in the bladder during cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Dmochowski and Gomelsky [ 9 ] suggested that CP/CPPS was another condition with prominent LUTS. The condition is typically accompanied by pain with ejaculation or in the perineal area.…”
Section: Discussionmentioning
confidence: 99%
“…Because there is no gold standard diagnostic test for CP/CPPS and because its etiology is largely unknown, this entity remains a diagnosis of exclusion. As with BPH, the symptoms of CP/CPPS can be present during the storage phase, can be present during the voiding phase, or can occur postmicturition [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha receptor antagonists decrease smooth muscle tone in the prostate and bladder neck [ 14 ]. Because LUTS in men have traditionally been attributed to BPH and obstructed urinary flow, pharmacological therapies have been aimed at improving urinary flow rates rapidly and optimizing voiding efficiency [ 15 ]. According to the European Association of Urology guidelines, alpha-blockers should be offered to men with moderate to severe LUTS and are considered the first-line drug treatment for these patients [ 16 ].…”
Section: Alpha Receptor Antagonistsmentioning
confidence: 99%